PENGEMBANGAN BAHAN AJAR IPA TERPADU BERBASIS MODEL DIFERENSIASI UNTUK MENINGKATKAN LITERASI SAINS FISIKA SISWA SMP - Kasmawati, Kasmawati; Nasution, Eni Sumanti; Nasution, Fauziah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
Scientific literacy is a high-level thinking skill, and according to PISA 2018, Indonesia is 70th out of 78 countries participating in the OECD, with an average score of 396. Low level of students' high-level thinking skills in Natural Sciences subjects can also be seen in the school exam results. National Standard at SMP/MTs in Padangsidimpuan. This research aims to develop integrated natural science teaching materials based on the Differentiated Learning Model and evaluate its feasibility and effectiveness. This research uses the ADDIE research and development model. The instrument used to obtain validity uses a questionnaire with a Likert scale and for the effectiveness of scientific literacy uses a scientific literacy test with multiple choices. The research results show validity of teaching materials with aspects of content suitability is 89.45%, presentation suitability is 92.00%, language assessment is 94.20%, and scientific literacy assessment is 85.88%, with very valid criteria. The effectiveness of teaching materials is shown by the difference in the average score between the experimental class (83.55) and the control class (75,00) at postest. Based on the mean calculation, the average of the experimental class posttest is higher than the average of the control class posttest, The concluded that the scientific literacy of experimental class students has increased more than that of control class students.